Hot melt adhesive, preparation method thereof and fuel cell membrane electrode
By adopting two-layer hot melt adhesive, using materials such as polyester resin and copolyester hot melt adhesive, strong bonding between PEN and PFSA is achieved, and the problems of poor bonding and crystal points in the prior art are solved, and are suitable for fuel cell membrane electrode packaging.
Patent Information
- Application Number
- CN202510113883.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The prior art has problems with monomer residues, toxicity, cost and heat and weather resistance when the bonding between PEN and PFSA, and the preparation method is not easy to control the reaction speed, which will bring a large number of crystal points during film formation, affecting actual application.
The hot melt adhesive with a two-layer structure is adopted. The first adhesive layer is composed of polyester resin, styrene-type thermoplastic elastomer, graft-type toughening agent, epoxy chain extender and organic solvent. The second adhesive layer is composed of ethylene-methyl acrylate copolymer, copolyester hot melt adhesive, ethylene-methyl acrylate-glycidyl methacrylate terpolymer, epoxy ring opening promoter and organic solvent. Good bonding between PEN and PFSA is achieved through lamination arrangement.
It realizes strong bonding between PEN and PFSA, soaked in a sulfuric acid aqueous solution of 95°C and pH=2 for more than 2000 hours without bubbles or cracking, and maintains good bonding performance, and has a crystalline point film formation, which is suitable for fuel cell membrane electrode packaging.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a hot melt adhesive and a preparation method thereof, and a fuel cell membrane electrode. Background Art
[0002] Membrane electrode (MEA) is the site of multiphase material transmission and electrochemical reaction in fuel cells, which determines the overall performance, durability, production efficiency and cost control of fuel cells. It is mainly made of catalyst, proton exchange membrane (PEM), gas diffusion layer and frame. Proton exchange membrane (PEM) is one of the core components of membrane electrode (MEA). It has extremely high proton conductivity, good chemical stability and strong hydrophilicity, and can also provide support for catalyst coating. At present, perfluorosulfonic acid proton membrane (PFSA) has been widely used due to its good thermal stability and chemical stability, high mechanical strength and high degree of industrialization.
[0003] In order to prevent gas leakage, improve the stability and durability of fuel cells, optimize performance and prevent chemical corrosion, the encapsulation of fuel cell membrane electrodes is very critical. In the structure of the membrane electrode, the frame film plays the following roles: supporting the membrane electrode, keeping the membrane electrode stiff, encapsulating, and sealing. The materials that can be used for the frame film include polyethylene naphthalate (PEN), polyphenylene sulfide (PPS), polyetherimide (PEI), polyimide (PI), polypropylene (PP), polyethylene terephthalate (PET), etc. Among them, PEN is the most commonly used, with high durability, high heat resistance and high cost performance. In order to achieve good encapsulation of the fuel cell membrane electrode, it is necessary to achieve the bonding of the frame film and the proton exchange membrane, that is, the bonding of PEN and PFSA.
[0004] At present, most of the acrylic adhesives are used to achieve the bonding of PEN and PFSA. For example, the acrylic adhesives disclosed in the Chinese patent applications with publication numbers CN115181533A and CN116525871A have good adhesion to PEN and PFSA. However, the problems of monomer residue, toxicity, cost, heat resistance and weather resistance limit its large-scale use. In the Chinese patent application with publication number CN116814183A, a hydrolysis-resistant hot melt adhesive layer is prepared by uniformly mixing polyester resin, epoxy resin, organic solvent, anti-hydrolysis agent, leveling agent and cross-linking agent, which has good adhesion to PEN and PFSA and excellent hydrolysis resistance. However, this preparation method is not easy to control the reaction speed, and a large number of crystal points will be brought when the film is formed, which cannot be used in conjunction with the membrane electrode process. In addition, the adhesive is brittle, and the brittle adhesive is easy to crack or fall off when an external force acts, which seriously affects its use effect.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a hot melt adhesive and a preparation method thereof and a fuel cell membrane electrode. The hot melt adhesive of the present invention can achieve good bonding to PEN and PFSA, and will not bubble or crack when immersed in a sulfuric acid aqueous solution at 95°C and pH=2 for more than 2000 hours, and can maintain good bonding performance, and the film is free of crystal points.
[0007] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a hot melt adhesive, comprising a first adhesive layer and a second adhesive layer stacked; The first adhesive layer comprises the following components by weight: 50-80 parts of polyester resin, 10-40 parts of styrene thermoplastic elastomer, 5-20 parts of grafted toughening agent, 0.1-1.5 parts of epoxy chain extender and 100-200 parts of first organic solvent; the polyester resin has a 160°C / 2.16kg melt index of ≥30g / 10min; The second adhesive layer includes the following components in parts by weight: 40 to 60 parts of ethylene-methyl acrylate copolymer, 20 to 40 parts of copolyester hot melt adhesive, 10 to 30 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 0.1 to 2 parts of epoxy ring-opening accelerator and 100 to 200 parts of a second organic solvent; in the ethylene-methyl acrylate-glycidyl methacrylate terpolymer, the content of GMA is 3wt% to 6wt%.
[0008] In a specific embodiment of the present invention, the styrene-based thermoplastic elastomer includes at least one of styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer and hydrogenated styrene-isoprene-styrene block copolymer.
[0009] In a specific embodiment of the present invention, the grafting unit of the grafted toughening agent is maleic anhydride and / or glycidyl methacrylate. Further, the grafted toughening agent is at least one of SEBS grafted with maleic anhydride and / or glycidyl methacrylate.
[0010] In a specific embodiment of the present invention, in the grafted toughening agent, the grafting rate of the grafted unit is ≥0.5%.
[0011] In a specific embodiment of the present invention, the epoxy chain extender has an epoxy equivalent of 200 to 600 g / mol.
[0012] In a specific embodiment of the present invention, the first organic solvent includes butanone and ethyl acetate. Further, in the first organic solvent, the mass ratio of butanone to ethyl acetate is (1-3):1.
[0013] In a specific embodiment of the present invention, the content of methyl acrylate in the ethylene-methyl acrylate copolymer is ≥20wt%.
[0014] In a specific embodiment of the present invention, the melting point of the copolyester hot melt adhesive is ≥110°C.
[0015] In a specific embodiment of the present invention, the epoxy ring-opening accelerator includes at least one of 2,4,6-tris(dimethylaminomethyl)phenol, N,N-dimethylbenzylamine and 1-benzyl-2-methylimidazole.
[0016] In a specific embodiment of the present invention, the second organic solvent includes ethyl acetate and acetone. Further, in the second solvent, the mass ratio of ethyl acetate to acetone is (1-5):1.
[0017] In a specific embodiment of the present invention, the thickness of the hot melt adhesive is 10-25 μm. Furthermore, the thickness of the first adhesive layer and the second adhesive layer are both ≥5 μm.
[0018] The second aspect of the present invention provides a method for preparing the hot melt adhesive of the first aspect of the present invention, comprising the following steps: (a) uniformly mixing the components of the first adhesive layer, applying and drying to obtain the first adhesive layer; (b) The components of the second adhesive layer are mixed evenly, coated on the surface of the first adhesive layer, and dried to obtain a hot melt adhesive.
[0019] The third aspect of the present invention provides a fuel cell membrane electrode, comprising the hot melt adhesive of the first aspect of the present invention.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The hot melt adhesive of the present invention has a two-layer structure, the first adhesive layer can be used to connect PEN, and the second adhesive layer can be used to connect PFSA, so that PEN and PFSA are connected through the hot melt adhesive of the present invention. The hot melt adhesive has a strong bonding effect on PEN, PFSA and the two adhesive layers of the hot melt adhesive. It does not bubble or crack after being immersed in a sulfuric acid aqueous solution at 95°C and pH=2 for more than 2000 hours, and still maintains good bonding performance; (2) The hot melt adhesive of the present invention has a simple preparation process, has no crystal points when coated, and can be produced continuously, and can be applied to the field of fuel cell membrane electrode packaging. DETAILED DESCRIPTION
[0021] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0022] The hot melt adhesive comprises a first adhesive layer and a second adhesive layer which are stacked; The first adhesive layer comprises the following components by weight: 50-80 parts of polyester resin, 10-40 parts of styrene thermoplastic elastomer, 5-20 parts of grafted toughening agent, 0.1-1.5 parts of epoxy chain extender and 100-200 parts of first organic solvent; the 160°C / 2.16kg melt index of the polyester resin is ≥30g / 10min; The second adhesive layer includes the following components in parts by weight: 40-60 parts of ethylene-methyl acrylate copolymer, 20-40 parts of copolyester hot melt adhesive, 10-30 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 0.1-2 parts of epoxy ring-opening accelerator and 100-200 parts of a second organic solvent; in the ethylene-methyl acrylate-glycidyl methacrylate terpolymer, the content of GMA is 3wt% to 6wt%.
[0023] The hot melt adhesive of the present invention has a two-layer structure, the first adhesive layer can be used to connect PEN, and the second adhesive layer can be used to connect PFSA, so that PEN and PFSA are connected through the hot melt adhesive of the present invention. The hot melt adhesive has a strong bonding effect on PEN, PFSA and the two adhesive layers of the hot melt adhesive. It does not bubble or crack when immersed in a sulfuric acid aqueous solution at 95°C and pH=2 for more than 2000 hours, and still maintains good bonding performance.
[0024] The first adhesive layer can be used to connect PEN. The polyester resin in the first adhesive layer has a similar chemical structure to PEN and has good adhesion to PEN. However, studies have found that the surface energy of PEN film is low and the rigidity is strong, and the wettability of ordinary polyester resin to PEN film is poor. The present invention uses a polyester resin with a melt index ≥ 30g / 10min (160℃ / 2.16kg) as the main material to improve its wettability to PEN film. For example, the melt index of the polyester resin can be 30g / 10min, 40g / 10min, 50g / 10min, 60g / 10min, 70g / 10min, 80g / 10min or a range composed of any two of them, thereby ensuring the wettability and bonding strength of the first adhesive layer to PEN.
[0025] Introducing styrene-based thermoplastic elastomers into the first adhesive layer can, on the one hand, improve the flexibility of the polyester resin; on the other hand, when preparing the coating, such as coating the first adhesive layer on a PEN substrate, the introduction of styrene-based thermoplastic elastomers can increase the initial adhesion of the first adhesive layer to PEN.
[0026] The introduction of an appropriate amount of graft toughening agent into the first adhesive layer helps to improve the compatibility of polyester resin and styrene thermoplastic elastomer. The introduction of epoxy chain extender can further form chemical bonds in the first adhesive layer to achieve chain extension, and can prevent the polyester resin from hydrolyzing or thermally degrading under long-term acid boiling conditions, so as to restore and improve mechanical properties and thermal properties. The first organic solvent is used to dissolve the remaining components in the first adhesive layer to ensure coating processability.
[0027] For example, in different embodiments, the amounts of the components in the first adhesive layer may be as follows, measured by weight: The amount of polyester resin can be 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or a range consisting of any two of them; the amount of styrene-based thermoplastic elastomer can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or a range consisting of any two of them; the amount of grafted toughening agent can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts or a range consisting of any two of them; the amount of epoxy chain extender can be 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts or a range consisting of any two of them; the amount of the first organic solvent can be 100 parts, 120 parts, 150 parts, 180 parts, 200 parts or a range consisting of any two of them.
[0028] The second adhesive layer can be used to connect PFSA. The ethylene-methyl acrylate copolymer in the second adhesive layer has a good initial bonding strength to PFSA, so ethylene-methyl acrylate copolymer is used as the main material for bonding PFSA. The appropriate amount of copolyester hot melt adhesive is introduced to increase the bonding strength between the first adhesive layer and the second adhesive layer; the study found that when the amount of copolyester hot melt adhesive is too small, it will significantly affect the bonding effect between the second adhesive layer and the first adhesive layer, and when the amount of copolyester hot melt adhesive is too much, it will affect the bonding between the second adhesive layer and PFSA. The present invention introduces an appropriate amount of copolyester hot melt adhesive into the second adhesive layer to ensure the bonding performance of the second adhesive layer to the first adhesive layer and PFSA. Ethylene-methyl acrylate-glycidyl methacrylate terpolymer can improve the compatibility of ethylene-methyl acrylate copolymer and copolyester hot melt adhesive, as well as the flexibility of the second adhesive layer. The epoxy ring-opening promoter can promote the epoxy group opening of the ethylene-methyl acrylate-glycidyl methacrylate terpolymer in the second adhesive layer. The second organic solvent is used to dissolve the remaining components in the second adhesive layer to ensure coating processability. The present invention further regulates the content of GMA in the ethylene-methyl acrylate-glycidyl methacrylate terpolymer to be 3wt% to 6wt%, for example, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt% or any two thereof, thereby helping to avoid the problem of film-forming crystal points on the basis of fully improving the compatibility of the second adhesive layer.
[0029] In a specific embodiment of the present invention, the styrene-based thermoplastic elastomer includes at least one of styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer and hydrogenated styrene-isoprene-styrene block copolymer, and further preferably includes at least one of hydrogenated styrene-butadiene-styrene block copolymer and hydrogenated styrene-isoprene-styrene block copolymer, thereby helping to further improve the long-term acid boiling resistance effect.
[0030] In a specific embodiment of the present invention, the grafting unit of the grafted toughening agent is maleic anhydride and / or glycidyl methacrylate. Further, the grafted toughening agent is at least one of SEBS grafted with maleic anhydride and / or glycidyl methacrylate.
[0031] In a specific embodiment of the present invention, in the grafted toughening agent, the grafting rate of the grafted unit is ≥0.5%, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2% or a range consisting of any two thereof.
[0032] In a specific embodiment of the present invention, in the epoxy chain extender, the epoxy equivalent is 200-600 g / mol, for example, it can be 200 g / mol, 250 g / mol, 300 g / mol, 350 g / mol, 400 g / mol, 450 g / mol, 500 g / mol, 550 g / mol, 600 g / mol or any two of them, so as to achieve appropriate chain extension to ensure strength, toughness and acid boiling resistance. Further, the epoxy chain extender includes but is not limited to at least one of BASF's epoxy chain extender ADR-4400 or BASF's epoxy chain extender ADR-4468.
[0033] In a specific embodiment of the present invention, the first organic solvent includes butanone and ethyl acetate. Further, in the first organic solvent, the mass ratio of butanone to ethyl acetate is (1-3) : 1, for example, it can be 1: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1 or a range consisting of any two of them. Studies have found that the first organic solvent is compounded with butanone and ethyl acetate, which, on the one hand, can have a high solubility for the remaining components used in the first adhesive layer; on the other hand, it has a moderate boiling point, and can ensure drying at an appropriate drying temperature, which is conducive to avoiding the generation of crystal points; furthermore, the solvent is convenient for post-processing.
[0034] In a specific embodiment of the present invention, the content of methyl acrylate in the ethylene-methyl acrylate copolymer is ≥20wt%, for example, it can be 20wt%, 22wt%, 25wt%, 28wt%, 30wt% or a range composed of any two thereof, thereby helping to ensure the initial bonding strength to PFSA and the bonding strength to the first bonding layer.
[0035] In a specific embodiment of the present invention, the melting point of the copolyester hot melt adhesive is ≥110°C, for example, it can be 110°C, 120°C, 130°C, 140°C, 150°C or a range consisting of any two thereof.
[0036] In a specific embodiment of the present invention, the epoxy ring-opening accelerator includes at least one of 2,4,6-tris(dimethylaminomethyl)phenol, N,N-dimethylbenzylamine and 1-benzyl-2-methylimidazole. The inventors of the present invention have found in their research that in order to further match the film appearance and adhesion, the epoxy ring-opening accelerator basically does not undergo a ring-opening reaction during the film-forming process, but undergoes a ring-opening reaction during the subsequent hot-pressing composite of PEN and PFSA and the long-term acid boiling process. At this time, the epoxy groups in the second adhesive layer will chemically react with the functional groups of the first adhesive layer, greatly increasing the bonding reliability of the first adhesive layer and the second adhesive layer, and at the same time increasing the bonding durability of the second adhesive layer and PFSA. The present invention has been found through experiments that the above epoxy ring-opening accelerator can achieve the above-mentioned expected effects.
[0037] In a specific embodiment of the present invention, the second organic solvent includes ethyl acetate and acetone. Further, in the second solvent, the mass ratio of ethyl acetate to acetone is (1-5) : 1, for example, it can be 1: 1, 2: 1, 3: 1, 4: 1, 5: 1 or any two of them. Studies have found that the second organic solvent is a compound of ethyl acetate and acetone. On the one hand, it can have a high solubility for the remaining components used in the second adhesive layer; on the other hand, it has a moderate boiling point, and can ensure drying at an appropriate drying temperature, which is conducive to avoiding the generation of crystal points; furthermore, the solvent is convenient for post-processing.
[0038] In a specific embodiment of the present invention, the thickness of the hot melt adhesive is 10-25 μm, for example, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 25 μm or any two thereof. Further, the thickness of the first adhesive layer and the second adhesive layer are both ≥ 5 μm, for example, they can be independently 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or any two thereof.
[0039] The second aspect of the present invention provides a method for preparing the hot melt adhesive of the first aspect of the present invention, comprising the following steps: (a) uniformly mixing the components of the first adhesive layer, applying and drying to obtain the first adhesive layer; (b) The components of the second adhesive layer are mixed evenly, applied on the surface of the first adhesive layer, and dried to obtain a hot melt adhesive.
[0040] In a specific embodiment of the present invention, in step (a), the uniform mixing comprises: mixing the polyester resin, the styrene-based thermoplastic elastomer, the grafted toughening agent, the epoxy chain extender, and the first organic solvent according to a proportion, and stirring at 400 to 1000 r / min until the components are dissolved.
[0041] In a specific embodiment of the present invention, in step (b), the uniform mixing comprises: mixing ethylene-methyl acrylate copolymer, copolyester hot melt adhesive, ethylene-methyl acrylate-glycidyl methacrylate terpolymer, epoxy ring-opening accelerator, and the second organic solvent according to a proportion, and stirring at 400 to 1000 r / min until each component is dissolved.
[0042] In a specific embodiment of the present invention, in step (a), coating includes: coating the mixed material on a PEN substrate. Further, the thickness of the PEN substrate may be 5 to 30 μm, but is not limited thereto.
[0043] In a specific embodiment of the present invention, in step (a), drying comprises: drying at 90-110° C. The drying time of step (a) is conventionally adjusted according to the volatilization of the first organic solvent in the coating after coating, until the first organic solvent is dried.
[0044] In a specific embodiment of the present invention, in step (b), drying includes: drying at 80-90° C. The drying time of step (b) is conventionally adjusted according to the volatilization of the second organic solvent in the coating after coating, until the second organic solvent is dried.
[0045] The third aspect of the present invention provides a fuel cell membrane electrode, comprising the hot melt adhesive of the first aspect of the present invention.
[0046] In a specific embodiment of the present invention, the fuel cell membrane electrode comprises a PFSA membrane and a PEN frame membrane, and the PFSA membrane and the PEN frame membrane are bonded by the hot melt adhesive of the present invention; the first bonding layer of the hot melt adhesive of the present invention is bonded to the PEN frame membrane, and the second bonding layer is bonded to the PFSA membrane.
[0047] The hot melt adhesive of the present invention can be used for packaging of fuel cell membrane electrodes, for example, it can be used for bonding PEN frame films and PFSA films of fuel cell membrane electrodes to achieve good packaging of fuel cell membrane electrodes.
[0048] Example 1 This embodiment provides a hot melt adhesive, including a first adhesive layer and a second adhesive layer that are stacked, the first adhesive layer has a thickness of 10 μm, and the second adhesive layer has a thickness of 10 μm.
[0049] The raw materials used in the first bonding layer include, by weight, 60 parts of polyester resin, 30 parts of styrene thermoplastic elastomer, 10 parts of grafted toughening agent, 0.5 parts of epoxy chain extender and 150 parts of the first organic solvent. Among them, the melt index (160°C / 2.16kg) of the polyester resin is 65g / 10min (brand name 3120H, manufacturer Guangdong Suntech New Materials Co., Ltd.); the styrene thermoplastic elastomer is hydrogenated styrene-butadiene-styrene block copolymer (SEBS) (brand name American Kraton G1641); the grafted toughening agent is maleic anhydride grafted SEBS (brand name American Kraton FG1901, maleic anhydride grafting rate is 1.7%); the epoxy chain extender is German BASF ADR-4468; the first organic solvent is a mixture of butanone and ethyl acetate in a mass ratio of 2:1.
[0050] The raw materials used in the second adhesive layer include, by weight: 50 parts of ethylene-methyl acrylate copolymer, 30 parts of copolyester hot melt adhesive, 20 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 0.5 parts of epoxy ring-opening accelerator, and 150 parts of the second organic solvent. Among them, the methyl acrylate content of the ethylene-methyl acrylate copolymer is 25wt% (brand name is Dow AC 1125 of the United States); the melting point of the copolyester hot melt adhesive is 130°C (brand name is HT-5130, manufacturer is Wenzhou Huate Hot Melt Adhesive Co., Ltd.); the GMA content of the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 6wt% (brand name is Sumitomo BF-7M of Japan); the epoxy ring-opening accelerator is 2,4,6-tris (dimethylaminomethyl) phenol; the second organic solvent is a mixture of ethyl acetate and acetone in a mass ratio of 2:1.
[0051] The method for preparing the hot melt adhesive of this embodiment comprises the following steps: (1) Stirring the raw materials of the first adhesive layer according to the proportion at a stirring speed of 600 r / min at room temperature until the materials are dissolved and mixed uniformly to obtain a first adhesive layer mixture; (2) coating the first adhesive layer mixture obtained in step (1) on the surface of a 25 μm thick PEN substrate, and then placing it in an oven at a temperature of 100° C. to obtain a PEN-first adhesive layer composite structure after the organic solvent is dried, wherein the thickness of the first adhesive layer is 10 μm; (3) Stirring the raw materials of the second adhesive layer according to the proportion at a stirring speed of 800 r / min at room temperature until the materials are dissolved and mixed evenly, thereby obtaining a second adhesive layer mixture; (4) The second adhesive layer mixture prepared in step (3) is coated on the surface of the first adhesive layer of the composite structure obtained in step (2), and then placed in an oven at a temperature of 80° C. to obtain a PEN-first adhesive layer-second adhesive layer composite structure after the organic solvent is dried. The thickness of the second adhesive layer is 10 μm.
[0052] Example 2 This embodiment provides a hot melt adhesive, including a first adhesive layer and a second adhesive layer that are stacked, the thickness of the first adhesive layer is 8 μm, and the thickness of the second adhesive layer is 7 μm.
[0053] The raw materials used in the first bonding layer include 70 parts of polyester resin, 25 parts of styrene thermoplastic elastomer, 5 parts of grafted toughening agent, 0.8 parts of epoxy chain extender and 120 parts of the first organic solvent by weight. Among them, the melt index (160℃ / 2.16kg) of the polyester resin is 45g / 10min (brand name 3150H, manufacturer Guangdong Suntech New Materials Co., Ltd.); the styrene thermoplastic elastomer is hydrogenated styrene-isoprene-styrene block copolymer (SEPS) (brand name Baling Petrochemical YH-4053); the grafted toughening agent is maleic anhydride grafted SEBS (brand name Taiwan Formosa Plastics 7126, maleic anhydride grafting rate is 1.6%); the epoxy chain extender is German BASF ADR-4400; the first organic solvent is a mixture of butanone and ethyl acetate in a mass ratio of 3:1.
[0054] The raw materials used in the second adhesive layer include, by weight: 40 parts of ethylene-methyl acrylate copolymer, 35 parts of copolyester hot melt adhesive, 15 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 0.3 parts of epoxy ring-opening accelerator, and 180 parts of the second organic solvent. Among them, the methyl acrylate content of the ethylene-methyl acrylate copolymer is 29wt% (brand SK 29MA03T); the melting point of the copolyester hot melt adhesive is 126°C (brand Toyobo GM-913); the GMA content of the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 3wt% (brand Sumitomo BF-7L); the epoxy ring-opening accelerator is 1-benzyl-2-methylimidazole; and the second organic solvent is a mixture of ethyl acetate and acetone in a mass ratio of 5:1.
[0055] The method for preparing the hot melt adhesive of this embodiment comprises the following steps: (1) Stirring the raw materials of the first adhesive layer according to the proportion at a stirring speed of 500 r / min at room temperature until the materials are dissolved and mixed evenly to obtain a first adhesive layer mixture; (2) coating the first adhesive layer mixture obtained in step (1) on the surface of a 25 μm thick PEN substrate, and then placing the mixture in an oven at a temperature of 90° C. to obtain a PEN-first adhesive layer composite structure after drying the organic solvent. The thickness of the first adhesive layer is 8 μm; (3) Stirring the raw materials of the second adhesive layer according to the proportion at a stirring speed of 600 r / min at room temperature until the materials are dissolved and mixed evenly, thereby obtaining a second adhesive layer mixture; (4) The second adhesive layer mixture prepared in step (3) is coated on the surface of the first adhesive layer of the composite structure obtained in step (2), and then placed in an oven at a temperature of 85° C. to obtain a PEN-first adhesive layer-second adhesive layer composite structure after the organic solvent is dried. The thickness of the second adhesive layer is 7 μm.
[0056] Example 3 This embodiment provides a hot melt adhesive, including a first adhesive layer and a second adhesive layer that are stacked, the first adhesive layer has a thickness of 9 μm, and the second adhesive layer has a thickness of 12 μm.
[0057] The raw materials used in the first adhesive layer include, by weight, 50 parts of polyester resin, 35 parts of styrene thermoplastic elastomer, 15 parts of grafted toughening agent, 1 part of epoxy chain extender and 100 parts of the first organic solvent. Among them, the melt index (160°C / 2.16kg) of the polyester resin is 37g / 10min (brand SK EH100); the styrene thermoplastic elastomer is hydrogenated styrene-butadiene-styrene block copolymer (SEBS) (brand American Kraton G1651); the grafted toughening agent is maleic anhydride grafted SEBS (brand American Kraton RP6670, maleic anhydride grafting rate is 1.1%); the epoxy chain extender is German BASF ADR-4468; the first organic solvent is a mixture of butanone and ethyl acetate in a mass ratio of 1:1.
[0058] The raw materials used in the second adhesive layer include, by weight: 45 parts of ethylene-methyl acrylate copolymer, 25 parts of copolyester hot melt adhesive, 30 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 0.8 parts of epoxy ring-opening accelerator, and 120 parts of the second organic solvent. Among them, the methyl acrylate content of the ethylene-methyl acrylate copolymer is 21.5wt% (brand ExxonMobil TC120); the melting point of the copolyester hot melt adhesive is 112°C (brand Toyobo GM-900); the GMA content of the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 6wt% (brand Sumitomo BF-7M); the epoxy ring-opening accelerator is N,N-dimethylbenzylamine; and the second organic solvent is a mixture of ethyl acetate and acetone in a mass ratio of 3:1.
[0059] The method for preparing the hot melt adhesive of this embodiment comprises the following steps: (1) Stirring the raw materials of the first adhesive layer according to the proportion at a stirring speed of 700 r / min at room temperature until the materials are dissolved and mixed evenly to obtain a first adhesive layer mixture; (2) coating the first adhesive layer mixture prepared in step (1) on the surface of a 25 μm thick PEN substrate, and then placing the substrate in an oven at a temperature of 95° C. to obtain a PEN-first adhesive layer composite structure after drying the organic solvent. The thickness of the first adhesive layer is 9 μm; (3) Stirring the raw materials of the second adhesive layer according to the proportion at a stirring speed of 1000 r / min at room temperature until the materials are dissolved and mixed evenly to obtain a second adhesive layer mixture; (4) The second adhesive layer mixture prepared in step (3) is coated on the surface of the first adhesive layer of the composite structure obtained in step (2), and then placed in an oven at a temperature of 90° C. to obtain a PEN-first adhesive layer-second adhesive layer composite structure after the organic solvent is dried. The thickness of the second adhesive layer is 12 μm.
[0060] Example 4 This embodiment provides a hot melt adhesive, including a first adhesive layer and a second adhesive layer that are stacked, the thickness of the first adhesive layer is 6 μm, and the thickness of the second adhesive layer is 8 μm.
[0061] The raw materials used in the first adhesive layer include, by weight, 65 parts of polyester resin, 20 parts of styrene thermoplastic elastomer, 15 parts of grafted toughening agent, 1.2 parts of epoxy chain extender and 140 parts of the first organic solvent. Among them, the melt index (160°C / 2.16kg) of the polyester resin is 65g / 10min (brand name 3120H, manufacturer Guangdong Suntech New Materials Co., Ltd.); the styrene thermoplastic elastomer is hydrogenated styrene-isoprene-styrene block copolymer (SEPS) (brand name Baling Petrochemical YH-4051); the grafted toughening agent is glycidyl methacrylate grafted SEBS (manufacturer Wuxi Zhiyuan Chemical Co., Ltd., glycidyl methacrylate grafting rate is 1.5%); the epoxy chain extender is BASF ADR-4400 of Germany; the first organic solvent is a mixture of butanone and ethyl acetate in a mass ratio of 5:2.
[0062] The raw materials used in the second adhesive layer include, by weight: 55 parts of ethylene-methyl acrylate copolymer, 20 parts of copolyester hot melt adhesive, 25 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 1.2 parts of epoxy ring-opening accelerator, and 100 parts of the second organic solvent. Among them, the methyl acrylate content of the ethylene-methyl acrylate copolymer is 30wt% (brand name is Dow AC 1330 of the United States); the melting point of the copolyester hot melt adhesive is 125°C (brand name is Toyobo 30P); the GMA content of the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 3wt% (brand name is Sumitomo BF-7L of Japan); the epoxy ring-opening accelerator is 2,4,6-tris (dimethylaminomethyl) phenol; and the second organic solvent is a mixture of ethyl acetate and acetone in a mass ratio of 1:1.
[0063] The method for preparing the hot melt adhesive of this embodiment comprises the following steps: (1) Stirring the raw materials of the first adhesive layer according to the proportion at a stirring speed of 800 r / min at room temperature until the materials are dissolved and mixed uniformly to obtain a first adhesive layer mixture; (2) coating the first adhesive layer mixture prepared in step (1) on the surface of a 25 μm thick PEN substrate, and then placing the substrate in an oven at a temperature of 105° C. to obtain a PEN-first adhesive layer composite structure after drying the organic solvent. The thickness of the first adhesive layer is 6 μm; (3) Stirring the raw materials of the second adhesive layer according to the proportion at a stirring speed of 500 r / min at room temperature until the materials are dissolved and mixed evenly, thereby obtaining a second adhesive layer mixture; (4) The second adhesive layer mixture prepared in step (3) is coated on the surface of the first adhesive layer of the composite structure obtained in step (2), and then placed in an oven at a temperature of 80° C. to obtain a PEN-first adhesive layer-second adhesive layer composite structure after the organic solvent is dried. The thickness of the second adhesive layer is 8 μm.
[0064] Example 5 This embodiment provides a hot melt adhesive, including a first adhesive layer and a second adhesive layer that are stacked, the first adhesive layer has a thickness of 12 μm, and the second adhesive layer has a thickness of 6 μm.
[0065] The raw materials used in the first bonding layer include, by weight, 80 parts of polyester resin, 10 parts of styrene thermoplastic elastomer, 10 parts of grafted toughening agent, 0.3 parts of epoxy chain extender and 180 parts of the first organic solvent. Among them, the melt index (160°C / 2.16kg) of the polyester resin is 45g / 10min (brand name 3150H, manufacturer Guangdong Suntech New Materials Co., Ltd.); the styrene thermoplastic elastomer is hydrogenated styrene-butadiene-styrene block copolymer (SEBS) (brand name American Kraton G1642); the grafted toughening agent is maleic anhydride grafted SEBS (brand name Taiwan Formosa Plastics 7131, maleic anhydride grafting rate is 1.3%); the epoxy chain extender is German BASF ADR-4468; the first organic solvent is a mixture of butanone and ethyl acetate in a mass ratio of 7:2.
[0066] The raw materials used in the second adhesive layer include, by weight: 60 parts of ethylene-methyl acrylate copolymer, 25 parts of copolyester hot melt adhesive, 15 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 1.5 parts of epoxy ring-opening accelerator, and 200 parts of the second organic solvent. Among them, the methyl acrylate content of the ethylene-methyl acrylate copolymer is 24wt% (the brand is Dow AC 1224 of the United States); the melting point of the copolyester hot melt adhesive is 122°C (the brand is SK EH400); the GMA content of the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 6wt% (the brand is Sumitomo BF-7M of Japan); the epoxy ring-opening accelerator is 1-benzyl-2-methylimidazole; and the second organic solvent is a mixture of ethyl acetate and acetone in a mass ratio of 4:1.
[0067] The method for preparing the hot melt adhesive of this embodiment comprises the following steps: (1) Stirring the raw materials of the first adhesive layer according to the proportion at a stirring speed of 900 r / min at room temperature until the materials are dissolved and mixed evenly to obtain a first adhesive layer mixture; (2) coating the first adhesive layer mixture obtained in step (1) on the surface of a 25 μm thick PEN substrate, and then placing the substrate in an oven at a temperature of 110° C. to obtain a PEN-first adhesive layer composite structure after drying the organic solvent. The thickness of the first adhesive layer is 12 μm. (3) Stirring the raw materials of the second adhesive layer according to the proportion at a stirring speed of 700 r / min at room temperature until the materials are dissolved and mixed evenly, thereby obtaining a second adhesive layer mixture; (4) The second adhesive layer mixture prepared in step (3) is coated on the surface of the first adhesive layer of the composite structure obtained in step (2), and then placed in an oven at a temperature of 85° C. to obtain a PEN-first adhesive layer-second adhesive layer composite structure after the organic solvent is dried. The thickness of the second adhesive layer is 6 μm.
[0068] Example 6 This embodiment provides a hot melt adhesive, including a first adhesive layer and a second adhesive layer that are stacked, the first adhesive layer has a thickness of 7 μm, and the second adhesive layer has a thickness of 15 μm.
[0069] The raw materials used in the first adhesive layer include, by weight, 55 parts of polyester resin, 25 parts of styrene thermoplastic elastomer, 20 parts of grafted toughening agent, 0.6 parts of epoxy chain extender and 200 parts of the first organic solvent. Among them, the melt index (160°C / 2.16kg) of the polyester resin is 37g / 10min (brand name SK EH100); the styrene thermoplastic elastomer is hydrogenated styrene-isoprene-styrene block copolymer (SEPS) (brand name Baling Petrochemical YH-4052); the grafted toughening agent is glycidyl methacrylate grafted SEBS (manufacturer is Wuxi Zhiyuan Chemical Co., Ltd., glycidyl methacrylate grafting rate is 1.5%); the epoxy chain extender is BASF ADR-4400 of Germany; the first organic solvent is a mixture of butanone and ethyl acetate in a mass ratio of 7:3.
[0070] The raw materials used in the second adhesive layer include, by weight: 52 parts of ethylene-methyl acrylate copolymer, 26 parts of copolyester hot melt adhesive, 22 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 1.8 parts of epoxy ring-opening accelerator, and 140 parts of the second organic solvent. Among them, the methyl acrylate content of the ethylene-methyl acrylate copolymer is 24wt% (brand name is Dow AC 1224 of the United States); the melting point of the copolyester hot melt adhesive is 143°C (brand name is Toyobo GM-400); the GMA content of the ethylene-methyl acrylate-glycidyl methacrylate terpolymer is 3wt% (brand name is Sumitomo BF-7L of Japan); the epoxy ring-opening accelerator is N,N-dimethylbenzylamine; and the second organic solvent is a mixture of ethyl acetate and acetone in a mass ratio of 5:2.
[0071] The method for preparing the hot melt adhesive of this embodiment comprises the following steps: (1) Stirring the raw materials of the first adhesive layer according to the proportion at a stirring speed of 1000 r / min at room temperature until the materials are dissolved and mixed evenly to obtain a first adhesive layer mixture; (2) coating the first adhesive layer mixture prepared in step (1) on the surface of a 25 μm thick PEN substrate, and then placing the mixture in an oven at a temperature of 95° C. to obtain a PEN-first adhesive layer composite structure after drying the organic solvent. The thickness of the first adhesive layer is 7 μm; (3) Stirring the raw materials of the second adhesive layer according to the proportion at a stirring speed of 900 r / min at room temperature until the materials are dissolved and mixed evenly, thereby obtaining a second adhesive layer mixture; (4) The second adhesive layer mixture prepared in step (3) is coated on the surface of the first adhesive layer of the composite structure obtained in step (2), and then placed in an oven at a temperature of 90° C. to obtain a PEN-first adhesive layer-second adhesive layer composite structure after the organic solvent is dried. The thickness of the second adhesive layer is 15 μm.
[0072] Comparative Example 1 Comparative Example 1 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the raw materials used for the first adhesive layer do not contain styrene-based thermoplastic elastomer and grafted toughening agent, and the rest are the same as Example 1.
[0073] In terms of weight, the raw materials used in the first adhesive layer of Comparative Example 1 include: 100 parts of polyester resin, 0.5 parts of epoxy chain extender and 150 parts of the first organic solvent.
[0074] Comparative Example 2 Comparative Example 2 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the raw material used for the first adhesive layer does not contain a grafted toughening agent, and the rest is the same as Example 1.
[0075] In terms of weight, the raw materials used in the first adhesive layer of Comparative Example 2 include: 70 parts of polyester resin, 30 parts of styrene-based thermoplastic elastomer, 0.5 parts of epoxy chain extender and 150 parts of the first organic solvent.
[0076] Comparative Example 3 Comparative Example 3 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the raw materials used for the first adhesive layer do not contain epoxy chain extender, and the rest is the same as Example 1.
[0077] In terms of weight, the raw materials used in the first adhesive layer of Comparative Example 3 include: 60 parts of polyester resin, 30 parts of styrene-based thermoplastic elastomer, 10 parts of grafted toughening agent and 150 parts of the first organic solvent.
[0078] Comparative Example 4 Comparative Example 4 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the raw materials used for the second adhesive layer do not contain copolyester hot melt adhesive, ethylene-methyl acrylate-glycidyl methacrylate terpolymer and epoxy ring-opening accelerator, and the rest are the same as Example 1.
[0079] In parts by weight, the raw materials used for the second adhesive layer of Comparative Example 4 include: 100 parts of ethylene-methyl acrylate copolymer and 150 parts of the second organic solvent.
[0080] Comparative Example 5 Comparative Example 5 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the raw material used for the second adhesive layer does not contain copolyester hot melt adhesive, and the rest is the same as Example 1.
[0081] In parts by weight, the raw materials used for the second adhesive layer of Comparative Example 5 include: 80 parts of ethylene-methyl acrylate copolymer, 20 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 0.5 parts of epoxy ring-opening accelerator and 150 parts of the second organic solvent.
[0082] Comparative Example 6 Comparative Example 6 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the raw material used for the second adhesive layer does not contain ethylene-methyl acrylate-glycidyl methacrylate terpolymer, and the rest is the same as Example 1.
[0083] In terms of weight, the raw materials used in the second adhesive layer of Comparative Example 6 include: 70 parts of ethylene-methyl acrylate copolymer, 30 parts of copolyester hot melt adhesive, 0.5 parts of epoxy ring-opening accelerator and 150 parts of the second organic solvent.
[0084] Comparative Example 7 Comparative Example 7 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the type of ethylene-methyl acrylate-glycidyl methacrylate terpolymer used in the second adhesive layer is different, and the rest is the same as Example 1.
[0085] The second adhesive layer of Comparative Example 7 uses ethylene-methyl acrylate-glycidyl methacrylate terpolymer with a GMA content of 8 wt % (brand number: French Arkema AX 8900).
[0086] Comparative Example 8 Comparative Example 8 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the raw materials used for the second adhesive layer do not contain an epoxy ring-opening accelerator, and the rest is the same as Example 1.
[0087] In parts by weight, the raw materials used for the second adhesive layer of Comparative Example 8 include: 50 parts of ethylene-methyl acrylate copolymer, 30 parts of copolyester hot melt adhesive, 20 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer and 150 parts of a second organic solvent.
[0088] Comparative Example 9 Comparative Example 9 refers to the hot melt adhesive and preparation method thereof of Example 1, except that the type of polyester resin used in the first adhesive layer is different, and the rest is the same as Example 1.
[0089] The polyester resin used in the first adhesive layer of Comparative Example 9 has a melt index (160°C / 2.16kg) of 15 g / 10 min (brand name HT-5120-C, manufacturer: Wenzhou Huate Hot Melt Adhesive Co., Ltd.).
[0090] Experimental example The hot melt adhesives obtained in the embodiments and comparative examples were respectively made into the following composite structure samples: PEN / hot melt adhesive / hot melt adhesive / PEN (PEN / first adhesive layer / second adhesive layer / second adhesive layer / first adhesive layer / PEN), PEN / hot melt adhesive / PFSA (PEN / first adhesive layer / second adhesive layer / PFSA), PEN / hot melt adhesive / PFSA / hot melt adhesive / PEN (PEN / first adhesive layer / second adhesive layer / PFSA / second adhesive layer / first adhesive layer / PEN); wherein, the thickness of PEN is 25 μm, and the thickness of PFSA is 15 μm; the composite structure specimens were obtained by compounding at a compounding temperature of 135°C and a compounding pressure of 0.6 MPa for 10 s.
[0091] The composite structure samples of PEN / hot melt adhesive / hot melt adhesive / PEN and PEN / hot melt adhesive / PFSA were all left with peeling openings to examine their initial peel strength and peel strength after acid boiling for 2000 hours; The composite structure sample of PEN / hot melt adhesive / PFSA / hot melt adhesive / PEN has no peeling opening and is a sealed structure. The presence of bubbles and cracks after acid boiling for 2000 hours was examined.
[0092] Specifically, the initial peel strength refers to: the peel strength measured after the prepared composite structure sample is cooled to room temperature; The peel strength after acid boiling for 2000 hours refers to the peel strength of the composite structure sample after it is cooled to room temperature, immersed in a sulfuric acid aqueous solution at 95°C and pH=2 for 2000 hours, taken out, wiped dry, and cooled to room temperature. Whether there are bubbles or cracks after acid boiling for 2000 hours means: after cooling the prepared composite structure sample to room temperature, soak it in a sulfuric acid aqueous solution at 95°C and pH=2 for 2000 hours, take it out, wipe the acid solution dry and cool it to room temperature, observe the appearance of the sample in a well-lit place to check whether there are bubbles, and bend the sample in half to check whether it is cracked; Whether the film has crystal points refers to: placing the PEN / hot melt adhesive composite structure prepared in different embodiments and comparative examples under light to detect the number of crystal points. If there are no crystal points with a diameter greater than 1 mm and the number of crystal points with a diameter of 0.5 to 1 mm is less than 5 per square meter, it means that the film has no crystal points. Otherwise, it means that the film has crystal points.
[0093] The test results are shown in Table 1. The test method for peel strength is based on GB / T GB8808-88 "Peeling test method for soft composite plastic materials".
[0094] Table 1 Test results of various embodiments and comparative examples
[0095] From the test results of Example 1 and Comparative Examples 1 to 9, it can be seen that the styrene-based thermoplastic elastomer improves the flexibility of the polyester resin without affecting its bonding effect on PEN; the grafted toughening agent improves the compatibility of the polyester resin and the styrene-based thermoplastic elastomer, preventing them from phase separation after long-term acid boiling and deteriorating their performance; the epoxy chain extender is used to restore and improve the mechanical and thermal properties of the polyester resin under long-term acid boiling; an appropriate amount of copolyester hot melt adhesive effectively improves the bonding strength between the second adhesive layer and the first adhesive layer; the ethylene-methyl acrylate-glycidyl methacrylate terpolymer and the epoxy ring-opening accelerator greatly improve the acid boiling resistance of the second adhesive layer and the first adhesive layer, and the second adhesive layer and PFSA.
[0096] From the test results of Examples 1 to 6, it can be seen that the hot melt adhesive with a two-layer structure of the present invention can achieve good bonding of PEN and PFSA, and does not bubble or crack after being immersed in a sulfuric acid aqueous solution at 95°C and pH=2 for more than 2000 hours, and still maintains good bonding performance. In addition, the preparation process of the hot melt adhesive of the present invention is simple, the solution is coated on the PEN substrate to form a film without crystal points, and can be produced continuously, and can be applied in the field of fuel cell membrane electrode packaging.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Hot melt adhesive, characterized in that: comprising a first adhesive layer and a second adhesive layer stacked; The first adhesive layer comprises the following components by weight: 50-80 parts of polyester resin, 10-40 parts of styrene thermoplastic elastomer, 5-20 parts of grafted toughening agent, 0.1-1.5 parts of epoxy chain extender and 100-200 parts of first organic solvent; the polyester resin has a 160°C / 2.16kg melt index of ≥30g / 10min; The second adhesive layer includes the following components in parts by weight: 40 to 60 parts of ethylene-methyl acrylate copolymer, 20 to 40 parts of copolyester hot melt adhesive, 10 to 30 parts of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, 0.1 to 2 parts of epoxy ring-opening accelerator and 100 to 200 parts of a second organic solvent; in the ethylene-methyl acrylate-glycidyl methacrylate terpolymer, the content of GMA is 3wt% to 6wt%.
2. The hot melt adhesive according to claim 1, characterized in that: The styrene-based thermoplastic elastomer includes at least one of a styrene-butadiene-styrene block copolymer, a hydrogenated styrene-butadiene-styrene block copolymer, a styrene-isoprene-styrene block copolymer, and a hydrogenated styrene-isoprene-styrene block copolymer.
3. The hot melt adhesive according to claim 1, characterized in that: The grafting unit of the grafted toughening agent is maleic anhydride and / or glycidyl methacrylate; In the grafted toughening agent, the grafting rate of the grafted unit is ≥0.5%.
4. The hot melt adhesive according to claim 1, characterized in that: In the epoxy chain extender, the epoxy equivalent is 200 to 600 g / mol.
5. The hot melt adhesive according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The first organic solvent includes butanone and ethyl acetate; (2) In the ethylene-methyl acrylate copolymer, the content of methyl acrylate is ≥ 20wt%.
6. The hot melt adhesive according to claim 1, characterized in that: The epoxy ring-opening accelerator includes at least one of 2,4,6-tris(dimethylaminomethyl)phenol, N,N-dimethylbenzylamine and 1-benzyl-2-methylimidazole.
7. The hot melt adhesive according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The melting point of the copolyester hot melt adhesive is ≥110°C; (2) The second organic solvent includes ethyl acetate and acetone.
8. The hot melt adhesive according to claim 1, characterized in that: The thickness of the hot melt adhesive is 10 to 25 μm; The thickness of the first adhesive layer and the second adhesive layer are both ≥5 μm.
9. The method for preparing the hot melt adhesive according to any one of claims 1 to 8, characterized in that: The steps include: (a) uniformly mixing the components of the first adhesive layer, applying and drying to obtain the first adhesive layer; (b) The components of the second adhesive layer are mixed evenly, coated on the surface of the first adhesive layer, and dried to obtain a hot melt adhesive.
10. A fuel cell membrane electrode, characterized in that: The invention comprises the hot melt adhesive according to any one of claims 1 to 8 or the hot melt adhesive prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Acrylate type hot melting frame film and manufacturing method thereof
CN116525871A
Frame adhesive tape for membrane electrode of fuel cell, membrane electrode, preparation method thereof and fuel cell
CN111777956A
Acrylate adhesive for bonding membrane electrode of fuel cell and preparation method of acrylate adhesive
CN115181533A
PES hot melt adhesive film as well as preparation method and application thereof
CN115584218A
Hydrolysis-resistant hot melt adhesive frame film and manufacturing method thereof
CN116814183A
Cited By
Hot melt adhesive and preparation method therefor, and fuel cell membrane electrode
WO2026157112A1